SINTESIS DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA KURKUMIN (3E,5E)-3,5-BIS(2â-HIDROKSIBENZILIDIN) -1-METILPIPERIDIN-4-ON - Hasanah, U.; Zamri, A.; Balatif, N.; Eryanti, Y. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The derivatives of curcumin are secondary metabolites belonging to the phenolicgroup. Some of them were reported to have biological activities such as anti-inflammatory, anticancer and antioxidant activities. In this study, a curcumin of(3E,5E)-3,5-bis(2â-hidroxybenzilidin)-1-metilpiperidin-4-onefrom1-methyl-4-piperidinone with 2-hydroxy benzaldehide has been successfully synthesized usingmicrowave irradiation method with NaOH (20%) as catalyst. Reaction was carried outfor 1 minute at 180 watt. The compound resulted was in the form of yellow crystalwith a yield of 72%. The compound was characterized by measuring its melting point,identifying by TLC, and elucidated by UV-Vis, FT-IR, MS, 1 H NMR, and 13 C NMR.Our result showed that the compound had the targeted molecule structure. Antibacterialtest was carried out using the agar diffusion method against Staphylococcus aureus,Escherichia coli, Bacillus subtilis, and Salmonella enteritidis. Overall, inhibition zoneranged from 6.5 to 10 mm and showed a very weak activity.